Turbulent flow in PVC pipes in water distribution systems. Issue 6 (2nd July 2020) - Carvajal, Juan; Zambrano, Willy; Gómez, Nicolás; Saldarriaga, Juan
ABSTRACT: Since the incorporation of PVC as pipe material in the second half of 20 th century, its use in the design, rehabilitation and expansion of Water Distribution Networks (WDS) has been widely assimilated. However, materials with higher roughness were more commonly used and with these materials were carried out the studies on which are based the most used design equations (Colebrook-White, Darcy-Weisbach and Hazen-Williams). In this work, the applicability of these equations is tested using PVC as the material to verify their precision. Measurements of pressure loss in different assemblies for extents of Reynolds numbers ranging from 3x10 4 to 5x10 5 and relative roughness between 6x10 -4 and 2x10 -3 were performed. For small diameters, Blasius and Prandtl–von Kármán equations can be used to calculate the friction factor. On the other hand, for larger diameters, the Colebrook-White equation correctly describes the relationship between the friction factor and the Reynolds number.